Contextual-based Open-Ended Model Improves Numeracy Skills of Grade IV Elementary School Students - Cintyawati, Ayu Ngurah Tri; Suniasih, Ni Wayan (Universitas Pendidikan Ganesha, 2024)
This research is motivated by numeracy problems that exist in elementary schools. Students tend to be more passive in learning mathematics because students have difficulty expressing mathematical arguments and ideas. Lack of innovation in the learning process makes students bored while studying. Therefore, an appropriate learning model is needed. This research aims to determine the effect of the contextual-based Open-Ended learning model on the numeracy abilities of fourth grade elementary school students. The type of research used is quasi-experimental research with the Nonequivalent Control Group Design type. The population in this study was all class IV elementary schools consisting of 9 classes with a total of 214 students. The sampling technique in this study was a cluster random sampling technique so that the sample obtained in this study was 28 people as the experimental group and 26 people as the control group. Numeracy ability data was obtained by administering an instrument in the form of an objective test in the form of a regular multiple choice. Student numeracy ability data was analyzed using the Polled Variance t-test. The results of the analysis show that there are significant differences between the experimental group and the control group. Thus, it can be concluded that the contextual-based Open-Ended model has an influence on the numeracy abilities of fourth grade elementary school students. The Contextual-based Open-Ended Model not only provides students with open problems related to real situations but can also guarantee openness to student activities in the learning process